Development and Validation of a HPLC Method of Quantification of Caffeine and EGCG in Green Tea (Camellia sinensis L.) Extract - Trong Bien, Tra; Thi Lan Phuong, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3DO - 10.25073/2588-1132/vnumps.4212, 2020)
This study investigates a simple high performance liquid chromatography (HPLC) in an isocratic eluent manner for quantification of caffeine and EGCG in green tea extract. The study separation system contained a C18-RP column (250 × 4.6 mm, 5 µm), a mobile phase of methanol/phosphoric acid/water (20/0.1/79.9, v/v) and a DAD detector at 280 nm. This system proves convenient for rapid routine analysis of caffeine and EGCG in green tea extract with good repeatability and accuracy. Keywords HPLC, caffeine, EGCG, green tea, extract. References [1] A. Chowdhury, J. Sarkar, T. Chakraborti, P.K. Pramanik, S. Chakraborti, Protective role of epigallocatechin-3-gallate in health and disease: A perspective, Biomedicine & Pharmacotherapy 78 (2016) 50-59. https://doi.org/10.1016/j.biopha.2015.12.013. [2] Y. Hara, Tea catechins and their applications as supplements and pharmaceutics, Pharmacological Research 64(2) (2011) 100-104. https://doi.org/10.1016/j.phrs.2011.03.018. [3] X. Jun, S. Zhao, B. Lu, R. Zhang, Y. Li, D. Shen, G. Zhou, Separation of major catechins from green tea by ultrahigh pressure extraction, International Journal of Pharmaceutics 386(1-2) (2010) 229-231. https://doi.org/10.1016/j.ijpharm.2009.10.035. [4] Z. Bedrood, M. Rameshrad, H. Hosseinzadeh, Toxicological effects of Camellia sinensis (green tea): A review, Phytotherapy Research 32(7) (2018) 1163-1180. https://doi.org/10.1002/ptr.6063. [5] J. Michael Glade, Caffeine-Not just a stimulant, Nutrition 26(10) (2010) 932-938. https://doi.org/10.1016/j.nut.2010.08.004. [6] MediGene AG. Press Release., MediGene AG Obtains Approval of Polyphenon®E Ointment in the USA, 2006. [7] Q.V. Vuong, V. Nguyen, J.B. Golding, P.D. Roach, The content of bioactive constituents as a quality index for Vietnamese teas, International Food Research Journal 18(1) (2011) 329-336. [8] Tran Trong Bien, Method for caffeine removal and catechins enrichment from green tea leaf, Master thesis, Hanoi University of Pharmacy, 2019 (In Vietnamese). [9] J. Joseph Dalluge, C. Bryant Nelson, Determination of tea catechins, Journal of Chromatography A 881 (2000) 411–424. https://doi.org/10.1016/S0021-9673(00)00062-5. [10] T. Shiono, et al., Selective decaffeination of tea extracts by montmorillonite, Journal of Food Engineering 200 (2017) 13-21. https://doi.org/10.1016/j.jfoodeng.2016.12.015.